2012
DOI: 10.1007/s12253-012-9560-6
|View full text |Cite
|
Sign up to set email alerts
|

High ADAM8 Expression is Associated with Poor Prognosis in Patients with Hepatocellular Carcinoma

Abstract: In this study,we investigated the ADAM8 expression in hepatocellular carcinoma (HCC) and its correlation with clinicopathologic features,including the survival of patients with HCC. Furthermore,we examined the biological processes regulated by ADAM8 during the development of using HepG2 cell line as a model system. We used immunohistochemistry to compare ADAM8 protein expression in HCC and normal liver tissues and further analyze the ADAM8 protein expression in clinicopathologically characterized 105 HCC cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 21 publications
4
38
1
Order By: Relevance
“…15 An earlier study by our group showed that high expression of serum miR-17-5p is associated with poor prognosis in HCC patients. 16 However, the precise roles of miR-17-5p in liver fibrosis remain obscure at present. Here, we showed that miR-17-5p is increased in TGF-β1-induced HSCs as well as in carbon tetrachloride (CCl 4 )-treated rat liver fibrotic tissues.…”
mentioning
confidence: 99%
“…15 An earlier study by our group showed that high expression of serum miR-17-5p is associated with poor prognosis in HCC patients. 16 However, the precise roles of miR-17-5p in liver fibrosis remain obscure at present. Here, we showed that miR-17-5p is increased in TGF-β1-induced HSCs as well as in carbon tetrachloride (CCl 4 )-treated rat liver fibrotic tissues.…”
mentioning
confidence: 99%
“…lncRNAs could be characterized by qRT-PCR, Northern blot analysis or in situ hybridization [63] . In recent years, studies have shown that there are a large number of abnormally expressed miRNA in the serum of patients with HCC; some with low-level expressions of miR-16, let-7f, miR-21, miR-139, miR-101, miR-122 and miR-1, and some with high-level expressions of miR-17-5p, which probably indicated the recurrence of HBV-related HCC prognosis [85] . Tan et al also identified that the miRNAs are differentially expressed in cirrhosis that evolved into HBV-related HCC by analyzing miRNAs that exhibit differential expressions such as miR-122-5p, miR-199a-5p, miR-486-5p, miR-193b-5p, miR-206, miR-141-3p, miR-192-5p and miR-26a-5p [86] .…”
Section: Serum Mirnas Diagnosis and Prognosis In Hccmentioning
confidence: 99%
“…Hbx protein decreases levels of several tumor suppressor miRNAs, such as miR-34 and let-7, 37 while HBx RNA directly downregulates miR-15a and miR-16-1. 38 Moreover, upregulated gene, upregulation of which is induced by HBx, could induce miR-148a overexpression and promote cell cycle progression and cell migration. 39,40 The mechanisms of miRNA deregulation by hepatitis C virus have been less extensively studied.…”
Section: Involvement Of Mirna In Hccmentioning
confidence: 99%